A questão comunicacional da transmídia - Sousa, Frederico Duarte Pires de (2015)
It is assumed aim in this paper to consider the transmedia, and from this, the communication. We are calling by “communicational transmedia question” a hypothetical divergence that we suppose exist between the idea of communication which supports the concept of transmedia and the nature of communicational experience in the transmedia situation experience itself. At first, we will try to map and differentiate some concepts of transmedia and related terms – such as multimedia, crossmedia, hypermedia, media convergence etc. – and from this discussion extract or find the notion of communication at stake. Later, we will use a phenomenological approach and occupy by the eidetic analysis of a specific transmedia object – in this case, the franchise Injustice: God Among Us, by Warner Bros. In describing the experience of this phenomenon and with the aid of some central theses presents in Paul Ricoeur's work, we will seek to individuate what it says in the curse of experience about communication. Although to formulate the question may be established as the north of this dissertation, round, the dissertation itself is the formulation of the question.